2022
DOI: 10.1101/2022.07.29.501978
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Neural tracking of linguistic speech representations decreases with advancing age

Abstract: Background: Older adults process speech differently, but it is not yet clear how aging affects different levels of processing natural, continuous speech, both in terms of bottom-up acoustic analysis and top-down generation of linguistic-based predictions. We studied natural speech processing across the adult lifespan via EEG measurements of neural tracking. Goals: Our goals are to analyze the unique contribution of linguistic speech processing across the adult lifespan using natural speech, while controlling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 113 publications
0
6
0
Order By: Relevance
“…Finally, we compare the linear forward model to MI in a group study. In a recent comparison, Gillis et al (2022) found higher neural envelope tracking for younger listeners compared to older adults. We replicated these results (Wilcoxon signed-rank test, W=95, p=0.039, Figure 6A).…”
Section: Resultsmentioning
confidence: 92%
See 3 more Smart Citations
“…Finally, we compare the linear forward model to MI in a group study. In a recent comparison, Gillis et al (2022) found higher neural envelope tracking for younger listeners compared to older adults. We replicated these results (Wilcoxon signed-rank test, W=95, p=0.039, Figure 6A).…”
Section: Resultsmentioning
confidence: 92%
“…A popular feature of the linear TRF is that it allows for peak latency analyses. In this dataset, a shift in the latency of the first peak was observed as age increased (Gillis et al, 2022). We plotted this trend for the parieto-occipital (positive peak) and central (negative peak) channels in Figure 6C (Pearson's r=-0.27, p=0.048; r=-0.39, p=0.004, respectively).…”
Section: Application To Group Study: Healthy Agingmentioning
confidence: 88%
See 2 more Smart Citations
“…It is likely that for a model with fixed complexity, these paradigms require appreciably lower data quantities to achieve significant prediction accuracies, given their high speech intelligibility. Indeed, in the context of subject-specific models, several single-talker works have reported significant feature-specific contributions for higher-order features with as little as 12 minutes of data (e.g., Broderick et al, 2021; Gillis et al, 2022b). We chose to use a dual-talker paradigm in part because studies exploring neural correlates of speech perception difficulties are increasingly popular, making the present analyses more relevant to these investigators.…”
Section: Discussionmentioning
confidence: 99%